Reframing Reproduction
XV, 304 p.
Keywords: How do rapid social and technological changes shape reproductive realms today? This book considers the complex choices, anxieties and challenges that come alongside postmodern reproduction for women and men in the West. Topics include surrogacy, fatherhood, sperm banking, egg donation, contraception, breastfeeding, and postpartum body image.